Leverage points for resilience : Introducing the pyramid framework for strategic adaptation planning and assessment - Rosengren, Linda; Budhathoki, Karuna; Haapala, Juho; Soini, Katriina; Sell, Mila (Springer Nature, 2026)
Sustainability transformation is a rapidly evolving field, yet few studies have explored approaches for food system transformation. This study addresses that gap by designing and applying a pyramid framework that integrates the leverage point perspective with three resilience capacities: coping, adaptive, and transformative. The goal of the framework is to (1) shed light on root causes that shape resilience and (2) pinpoint effective entry points for strengthening resilience and driving transformation. Using qualitative methods, this study applied the framework to a food system in western Nepal, identifying eleven leverage points. Results showed that deep leverage points supported transformative capacity, while shallow ones reinforced coping and adaptive capacities. The pyramid framework balances immediate shock responses with long-term planning. This integrated approach mitigates trade-offs between resilience strategies, reducing maladaptation risks. The pyramid framework serves as a tool for ex-ante strategic adaptation planning and ex-post assessment and evaluation of resilience policy and interventions.
Keywords: food system transformation; resilience; leverage points; Nepal